Accuracy of the ultrasound attenuation coefficient for the evaluation of hepatic steatosis: a systematic review and meta-analysis of prospective studies - Jong Keon Jang; Sang Hyun Choi; Ji Sung Lee; So Yeon Kim; Seung Soo Lee; Kyung Won Kim (Ultrasonography, 2022)
Purpose The accurate detection and quantification of hepatic steatosis using a noninvasive method are important for the management of nonalcoholic fatty liver disease. We performed a systematic review and meta-analysis of the accuracy of the ultrasound-measured attenuation coefficient (AC) in the evaluation of hepatic steatosis. Methods The PubMed, Embase, and Cochrane databases were searched for prospective studies reporting the diagnostic accuracy of AC for assessing hepatic steatosis. The meta-analytic pooled sensitivity and specificity of AC for any grade of steatosis (S≥1) and advanced steatosis (S≥2) were estimated using a bivariate random-effects model. Meta-regression analysis was conducted to investigate the causes of heterogeneity among studies. Results Thirteen studies including 1,509 patients were identified. The pooled sensitivity and specificity of AC for S≥1 were 76% (95% confidence interval [CI], 73% to 80%; I2=43%) and 84% (95% CI, 77% to 89%; I2=74%), respectively, while for S≥2 they were 87% (95% CI, 83% to 91%; I2=0%) and 79% (95% CI, 75% to 83%; I2=59%), respectively. Study heterogeneity was associated with body mass index (BMI) and the prevalence of steatosis or significant fibrosis. Conclusion AC can be clinically useful for assessing hepatic steatosis, with good overall diagnostic performance. The data reported in the published literature differed according to BMI and the prevalence of steatosis or significant fibrosis, and careful interpretation with consideration of these factors might be needed.